John 20.19–31 in Ruthenian Didactic Gospels: Siltse’s Group and Other Textologically Related Groups - Kazarinova, Ksenija (Slavistica Vilnensis, 2023)
The article examines the gospel passage John 20.19-31, presented in the Ruthenian didactic gospels. The material is formed of 16 handwritten texts. They were divided into 8 groups which due to their common features form a single hypergroup. Unique insertions / omissions make distinctive features of the hypergroup. There are three significant insertions: a) the words тыми словы [in these words] are met three times in the pericope; b) expansion of the confession of Apostle Thomas in John 20.28; c) expansion of the general confession in John 20.31. The omissions are noted a) in John 20.20, where the words “And when he had so said, he shewed unto them his hands and his side” are missing; b) in John 20.23 there are no words “and whose soever sins ye retain, they are retained”. The characteristic features of the hypergroup also include the use of Cyrillic numerals for в [12], as well as unique substitution from singular to plural in John 20.29. The data presented in the article allows us to trace close textual relationship between certain groups. The Siltsya’s and the Ipatiev, as well as the Hypatian and the Uhlya groups intersect because of common features. It is noted that the groups Historical (Ис) and Drogoyevsky (Дг) are the most remote from their conditional origin (Siltsya’s manuscript copy).